The glamour of strangeness artists and the last age of the exotic - James, Jamie (Farrar, Straus and Giroux, 2016)
"Exploration of a "rare, emotionally intense way of life" in which artists like Raden Saleh and Walter Spies abandon the cultures that created them and adopt an exotic alternative"--